(untitled) (Altre Modernità, 2025)
The article describes the characteristics and investigates the mechanisms behind the recent socio-literary intermedial phenomenon of romance, and it finally examines two case studies from the Italian landscape: Erin Doom and Rokia. The analysis focuses on their debut works, Fabbricante di lacrime (Magazzini Salani 2021) and The Truth Untold. La verità nascosta (Magazzini Salani 2022), and is conducted by relating the textual level with the contextual one, considering the entire production chain: from digital writing and promotion of texts on the social reading platform Wattpad to the composition and publication of books through the filters of traditional publishing.